The effect of ergonomic interventions on fatigue and musculoskeletal symptoms of university students during combined information and communication technologies tasks. - Depreli, Özde; Topcu, Zehra Güçhan; Angın, Ender; Değer, Ünal; Karaman, Ayşen (Work, 2025)
Background: As part of developments in educational systems, university students use combined information and communication technologies (ICT) tasks that may impact musculoskeletal (MSK) symptoms. Objective: This study aims to investigate the acute effect of ergonomic interventions applied during combined ICT tasks, which include reading electronic documents on a laptop and creating handwritten summaries after prolonged sitting in the lecture, on fatigue, discomfort, and musculoskeletal pain in university students. Methods: Fatigue severity was measured with the Modified Borg Scale, and pain, discomfort, and satisfaction with an ergonomic intervention were measured with the Visual Analogue Scale. Postural awareness was measured with the Postural Habits and Awareness Scale. The ergonomic intervention consisted of ergonomics education and in-class exercises. The Wilcoxon signed-rank test and T-Test were used to compare the posttest–pretest changes within the group. Results: A total of 44 university students, whose mean age was 22 ± 2 years, were included in this study. The ergonomic intervention was found to have a moderate effect on discomfort (r =.376) and a large effect on musculoskeletal pain (r =.570) and postural awareness (r =.608). Additionally, this intervention changed MSK pain by 32.5%, discomfort by 14.1%, and postural awareness by 60.8%. Conclusions: Ergonomic approaches positively affected musculoskeletal pain, discomfort, and postural awareness of students exposed to an intensive lecture with combined ICT tasks, whereas no effect was seen in the levels of fatigue and headache. Further research with a control group is needed.